Guidelines for parliamentary research services IFLA - Liên minh nghị viện thế giới
Well-resourced parliamentary research services are one of the building blocks of an effective parliament. They are of incalculable value as a source of independent, neutral and non-partisan analysis. They offer a safe space where parliamentarians from all political parties can ask questions and get answers they can trust. They contribute to a parliament’s autonomy by providing a reality check on the perspectives put forward by the executive branch of government, lobby groups and the news media. Their analysis informs a parliament’s legislative and oversight work and provides parliamentarians with the information they need to do their job well.